The Influence of Compression Stocking on Jumping Performance of Athlete - Salleh, Mohamed Najib; Mad Lazim, Halim; Lamsali, Hendrik; Salleh, Ahmad Faizal (IOP Publishing Ltd, 2018)
Evidence of compression stocking effectiveness are mixed, with some researchers suggests that the stocking can enhance performance while others dispute the finding. One of the factors that are thought to cause the mixed results is level of pressure used in their studies. This research had organized a test on fourteen athletes. Their body was scanned and a customized compression stocking which can exert pressure correspond to the intended one was developed. An experiment was conducted to measure the effect of wearing compression stocking on jumping performance. The results show mixed outcomes. For the female athlete, there is a significant difference between wearing and not wearing compression stocking (p<0.05) on knee power. However, there is no significant difference for male athletes whether wearing or not